Iron-based amorphous composite coating and preparation method and application thereof

By introducing Cr3C2 particles into the iron-based amorphous coating, the FeCrMo·Cr3C2 iron-based amorphous composite coating was prepared by supersonic flame spraying, which solved the short service life and resistance of the existing iron-based amorphous coating in harsh environments. The problem of insufficient abrasive performance has achieved a significant improvement in the hardness, wear resistance and corrosion resistance of the coating.

CN119506754AActive Publication Date: 2025-02-25LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411681839.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing iron-based amorphous coating has a short service life in harsh environments and does not have enough wear resistance, making it difficult to meet the industry's demand for improving coating performance.

Method used

Supersonic flame spraying method is used to introduce Cr3C2 particles into the iron-based amorphous coating to form a FeCrMo·Cr3C2 iron-based amorphous composite coating to improve the hardness, wear resistance and corrosion resistance of the coating.

Benefits of technology

It significantly improves the hardness, wear resistance and corrosion resistance of the iron-based amorphous composite coating, extends the service life of the metal matrix, and reduces the frequency of repair and replacement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506754A_ABST
    Figure CN119506754A_ABST
Patent Text Reader

Abstract

The invention provides an iron-based amorphous composite coating as well as a preparation method and application thereof, and relates to the technical field of amorphous coatings. The chemical composition of the iron-based amorphous composite coating provided by the invention comprises a FeCrMo amorphous coating and Cr3C2 particles which are dispersed in the FeCrMo amorphous coating, and the mass content of the Cr3C2 particles in the iron-based amorphous composite coating is 3-10%. The FeCrMo amorphous coating provided by the invention has the characteristics of high hardness, high wear resistance and more excellent corrosion resistance, does not contain toxic substances and is low in cost, and the prepared material has good mechanical properties of a metal matrix and excellent characteristics of an amorphous alloy. 3-10% of Cr3C2 particles with high hardness, chemical stability and corrosion resistance are added as a reinforcing phase, so that the hardness, wear resistance and corrosion resistance of the iron-based amorphous composite coating are remarkably improved, and the service life of a metal matrix under high-load and severe working conditions can be prolonged as a protective layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of amorphous coatings, and in particular to an iron-based amorphous composite coating and a preparation method and application thereof. Background Art

[0002] Due to its special atomic structure, amorphous alloys have many excellent physical, chemical and mechanical properties. For example, its strength reaches 2-5GPa, Vickers hardness reaches 7GPa, and elastic limit is as high as 2%, which are several times that of crystalline alloys, and it has excellent wear resistance and corrosion resistance. However, its critical size is small, and it is currently mainly used as a wear-resistant coating for large transformer cores and large oil drilling equipment. Among many amorphous systems, Fe-based amorphous coatings have the best strength, hardness and wear resistance. However, with the development of industry, a single iron-based amorphous coating can no longer meet the increasingly improved performance requirements of the industrial field for coating performance.

[0003] Compared with traditional iron-based amorphous alloy coatings, iron-based amorphous composite coatings significantly improve hardness, wear resistance and strength by introducing reinforcing phase materials into iron-based amorphous coatings, and the increased bonding strength with the substrate reduces the possibility of peeling, which can make it have a longer service life in harsh marine environment conditions. Moreover, compared with traditional and costly coating materials, iron-based amorphous alloy composite coatings are not only inexpensive, but also environmentally friendly, greatly avoiding risks to the environment and residents' health.

[0004] The preparation methods of iron-based amorphous composite coatings mainly include arc spraying, plasma spraying, explosion spraying, supersonic flame spraying, etc. Among them, supersonic flame spraying has the following advantages: (1) The spraying powder is heated to a high temperature state by a high-speed airflow, and quickly cooled to form a high-density amorphous structure, reducing the porosity of the coating; (2) Supersonic flame spraying can achieve uniform spraying in a larger area, can be sprayed on the surface of parts with various complex shapes, and the coating quality is more stable and reliable; (3) Supersonic flame spraying is more efficient and can be completed in a short time, saving time and cost and improving production efficiency. For example, the prior art discloses a NiCr-Cr3C2 coating prepared by supersonic flame spraying. The NiCr-Cr3C2 coating has a dense structure, low porosity, and a friction coefficient of 0.5 to 0.7. However, the wear resistance of the above-mentioned NiCr-Cr3C2 coating is not good enough, which limits its application. Summary of the invention

[0005] In view of this, the object of the present invention is to provide an iron-based amorphous composite coating and a preparation method and application thereof. The iron-based amorphous composite coating prepared by the present invention has excellent wear resistance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides an iron-based amorphous composite coating, the chemical composition of which includes a FeCrMo amorphous coating and Cr3C2 particles dispersed in the FeCrMo amorphous coating; the mass content of the Cr3C2 particles in the iron-based amorphous composite coating is 3-10%.

[0008] Preferably, the chemical composition of the FeCrMo amorphous coating includes, in terms of mass percentage, Cr 25-27%, Mo 16-18%, C 2.0-2.5%, B 2.0-2.2%, and Fe 50.3-55%.

[0009] Preferably, the thickness of the iron-based amorphous composite coating is 200-400 μm.

[0010] The present invention also provides a method for preparing the iron-based amorphous composite coating described in the above technical solution, comprising the following steps: using a mixed powder to perform supersonic flame spraying on the surface of a metal substrate to form an iron-based amorphous composite coating; the mixed powder comprises FeCrMo amorphous powder and Cr3C2 particles, and the mass content of Cr3C2 particles in the mixed powder is 3 to 10%.

[0011] Preferably, the particle size of the FeCrMo amorphous powder is 15-53 μm.

[0012] Preferably, the particle size of the Cr3C2 particles is 35-55 μm.

[0013] Preferably, the supersonic flame spraying adopts high-speed air fuel technology, and the process conditions include: oxygen flow rate 1500-2200SCFH, spraying distance 250-350mm, fuel flow rate 5-8GPH, powder feeding rate 30-40g / min, and carrier gas flow rate 10-15L / min.

[0014] Preferably, the fuel for supersonic flame spraying includes one or more of kerosene, propylene, natural gas and liquefied petroleum gas.

[0015] Preferably, the metal substrate is sandblasted and then preheated before use.

[0016] The present invention also provides the use of the iron-based amorphous composite coating described in the above technical solution or the iron-based amorphous composite coating prepared by the preparation method described in the above technical solution as a protective layer.

[0017] Compared with amorphous alloys of other systems, the FeCrMo amorphous coating provided by the present invention has high hardness, high wear resistance and better corrosion resistance, and can resist the erosion of corrosive media such as acids and alkalis very well; the FeCrMo iron-based amorphous coating does not contain toxic substances, thereby avoiding serious pollution to the environment; the research on the FeCrMo iron-based amorphous coating has a low cost, and can simultaneously take into account the good mechanical properties of the metal matrix and the excellent properties of the amorphous alloy. Cr3C2 particles belong to ceramic particles and have excellent hardness, chemical stability and corrosion resistance. The present invention successfully improves the pore state of the coating cross section and surface by adding 3-10wt% of Cr3C2 particles as a reinforcing phase in the FeCrMo amorphous coating, with fewer pores and a denser internal structure, which significantly improves the hardness, wear resistance and corrosion resistance of the iron-based amorphous composite coating. The iron-based amorphous composite coating (FeCrMo·Cr3C2) provided by the present invention as a protective layer can extend the service life of the metal substrate, especially the metal substrate under high load and harsh working conditions (such as pump valve components used in corrosive environments), and reduce its maintenance and replacement frequency. As shown in the test results of the embodiment, the hardness of the FeCrMo iron-based amorphous coating without the addition of Cr3C2 particles is 800HV, the friction coefficient is about 0.7, and the self-corrosion potential is -916.89V; while the microhardness of the iron-based amorphous composite coating containing 6wt% Cr3C2 particles reaches 962.7HV, the friction coefficient is reduced to about 0.2933, and the self-corrosion potential is -466.82V, indicating that the addition of Cr3C2 particles significantly enhances the hardness, wear resistance and corrosion resistance of the iron-based amorphous composite coating.

[0018] The present invention adopts the supersonic flame spraying method to prepare the iron-based amorphous composite coating on the surface of the metal substrate. The surface has a good melting state, a small amount of pores, a relatively dense internal structure, and contains a Cr3C2 phase. The amorphous rate is above 70%, and the iron-based amorphous composite coating has a high bonding strength with the metal substrate and is not easy to fall off. Moreover, the preparation method provided by the present invention has simple process, simple operation, low cost, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a SEM image of the X8-FeCrMoCB amorphous powder used in Examples 1 to 4 and Comparative Example 1;

[0020] Figure 2 is a SEM image of the Cr3C2 particles used in Examples 1 to 4;

[0021] Figure 3 This is a physical picture of the iron-based amorphous composite coating prepared in Example 1 before grinding and polishing;

[0022] Figure 4XRD patterns of the iron-based amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4;

[0023] Figure 5 The SEM images of the surface polished iron-based amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4, wherein (a) has a content of 3%, (b) has a content of 4.5%, (c) has a content of 6%, and (d) has a content of 7.5%;

[0024] Figure 6 The cross-sectional SEM images of the iron-based amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4, wherein (a) has a content of 3%, (b) has a content of 4.5%, (c) has a content of 6%, and (d) has a content of 7.5%;

[0025] Figure 7 BSE image (a) and EDS images (b-g) of the pores in the iron-based amorphous composite coating prepared in Example 4;

[0026] Figure 8 BSE image (a) and EDS images (b-g) of Cr3C2 particles in the iron-based amorphous composite coating prepared in Example 4;

[0027] Fig. 9 The microhardness diagrams of the iron-based amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4;

[0028] Fig.10 The friction coefficient of the iron-based amorphous composite coating with different Cr3C2 contents prepared in Examples 1 to 4 varies with time;

[0029] Fig.11 Wear quality diagram of the iron-based amorphous composite coating with different Cr3C2 contents prepared in Examples 1 to 4;

[0030] Fig.12 The microstructure diagrams of the iron-based amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4 after wear, wherein (a) the content is 3%, (b) the content is 4.5%, (c) the content is 6%, and (d) the content is 7.5%;

[0031] Fig.13 This is an EDS element analysis diagram of the surface characteristic area of ​​the iron-based amorphous composite coating prepared in Example 4;

[0032] Fig.14 The surface profiles of the iron-based amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 after friction and wear obtained by using a laser confocal microscope white light interferometer, wherein (a) the content is 3%, (b) the content is 4.5%, (c) the content is 6%, and (d) the content is 7.5%;

[0033] Fig.15 OCP curves of the iron-based amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4;

[0034] Fig.16 Polarization curves of the iron-based amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 and Comparative Example 1;

[0035] Fig.17 The Nyquist plots of the iron-based amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 and Comparative Example 1, and the inset is a schematic diagram of the coating equivalent circuit;

[0036] Fig.18 It is a schematic diagram of the packaging of the iron-based amorphous composite coating sample;

[0037] Fig.19 The statistical result diagram of weight loss of the iron-based amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 after immersion for 15 days;

[0038] Fig. 20 SEM images of the iron-based amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 after immersion for 1 day (a1 to d1), 7 days (a2 to d2), 15 days (a3 to d3) and after immersion for 15 days to remove corrosion products (a4 to d4), the contents of a1, a2, a3 and a4 are 3%, the contents of b1, b2, b3 and b4 are 4.5%, the contents of c1, c2, c3 and c4 are 6%, and the contents of d1, d2, d3 and d4 are 7%;

[0039] Fig.21 This is an EDS image of the corrosion products in the iron-based amorphous composite coating prepared in Example 4;

[0040] Fig. 22 This is the XRD pattern of the iron-based amorphous composite coating prepared in Example 4 after being corroded in simulated seawater;

[0041] Fig.23 Polarization curves of the iron-based amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 and Comparative Example 1 after immersion for 15 days;

[0042] Fig.24 Nyquist plots of the iron-based amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 and Comparative Example 1 after immersion for 15 days, and the inset is a schematic diagram of the coating equivalent circuit. DETAILED DESCRIPTION

[0043] The invention provides an iron-based amorphous composite coating, the chemical composition of which includes a FeCrMo amorphous coating and Cr3C2 particles dispersed in the FeCrMo amorphous coating; the content of Cr3C2 particles in the iron-based amorphous composite coating is 3-10wt%.

[0044] In the present invention, the mass content of Cr3C2 particles in the iron-based amorphous composite coating is 3-10%, and in specific embodiments, it can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%. In the present invention, the particle size of the Cr3C2 particles is preferably 35-55 μm.

[0045] Cr3C2 particles have extremely high hardness and excellent wear resistance. Their hardness is between 1800 and 2200 HV, which can effectively resist external wear and scratches. When Cr3C2 particles exist in the iron-based amorphous composite coating, Cr3C2 particles can form a hard protective layer to block the wear of the iron-based amorphous composite coating by external substances, thereby extending the service life of the iron-based amorphous composite coating. The melting point of Cr3C2 particles is 1890℃, and they show excellent stability and heat resistance under high temperature conditions, which makes Cr3C2 particles very suitable for use under high temperature conditions, such as aerospace, energy and petrochemical industries. In addition, Cr3C2 particles have excellent crack resistance. Cr3C2 particles can effectively avoid the cracking problem of the coating. This is because the hardness of Cr3C2 particles is very large. When cracks encounter Cr3C2 particles, the high hardness of the particles can well hinder the further expansion of the cracks, thereby slowing down the crack expansion speed and effectively resisting the propagation of cracks, which can improve the crack resistance of the coating. Cr3C2 particles show good chemical stability in a variety of chemical media and can resist corrosion and chemical erosion, which allows Cr3C2 particles to be used in coatings to protect substrates working in harsh environments (such as acid and alkali corrosion or corrosive gases). The present invention adds Cr3C2 particles as a reinforcing phase in the FeCrMo amorphous coating and controls the amount of Cr3C2 particles added, so that the iron-based amorphous composite coating has excellent wear resistance, hardness and corrosion resistance.

[0046] In the present invention, the chemical composition of the FeCrMo amorphous coating preferably includes, by mass percentage, Cr25-27%, Mo 16-18%, C 2.0-2.5%, B 2.0-2.2%, and Fe 50.3-55%. Compared with amorphous alloys of other systems, the FeCrMo amorphous coating provided by the present invention has high hardness, high wear resistance and better corrosion resistance, and can resist the erosion of corrosive media such as acids and alkalis very well. The excellent corrosion resistance of the FeCrMo amorphous alloy is due to the chromium oxide film on the surface of the alloy. The oxide film isolates the metal from the corrosive environment. There is no lattice mismatch between the surface oxide film and the amorphous alloy. The oxide film can achieve stress-free growth. Compared with the surface of the crystalline alloy, the surface oxide film of the amorphous alloy is more uniform, and the protective effect on the base metal is better. Due to the unique properties of the FeCrMo amorphous alloy, it is used as a protective coating with corrosion resistance, high hardness and wear resistance, and avoids the disadvantage of being limited to low-latitude shapes in practical applications.

[0047] In the present invention, the thickness of the iron-based amorphous composite coating is preferably 200-400 μm, and in specific embodiments may be 200 μm, 250 μm, 300 μm, 350 μm or 400 μm.

[0048] The present invention also provides a method for preparing the iron-based amorphous composite coating described in the above technical solution, comprising the following steps: using a mixed powder to perform supersonic flame spraying on the surface of a metal substrate to form an iron-based amorphous composite coating; the mixed powder comprises FeCrMo amorphous powder and Cr3C2 particles, and the mass content of Cr3C2 particles in the mixed powder is 3 to 10%.

[0049] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0050] In the present invention, the chemical composition of the FeCrMo amorphous powder is the same as the chemical composition of the FeCrMo amorphous coating, which will not be repeated here. In the present invention, the particle size of the FeCrMo amorphous powder is preferably 15 to 53 μm; the shape of the FeCrMo amorphous powder is preferably spherical. The FeCrMo amorphous powder of the above particle size used in the present invention has good fluidity, uniform particle size and good sphericity, which can effectively reduce the friction and interlocking phenomenon between particles, thereby greatly improving the fluidity during the spraying process; and the FeCrMo amorphous powder can pass through the nozzle smoothly, and achieve uniform spraying during the supersonic flame spraying process, ensuring that the coating is uniform and of good quality.

[0051] In the present invention, the particle size of the Cr3C2 particles is preferably 35 to 55 μm. The particle size of the FeCrMo amorphous powder used in the present invention is 15 to 53 μm, and the particle size of the Cr3C2 particles is 35 to 55 μm. The particle sizes of the Cr3C2 particles and the FeCrMo amorphous powder are matched. This particle size matching advantage helps to promote the good mixing of the reinforcing phase Cr3C2 particles and the FeCrMo amorphous powder, prevents the separation or uneven deposition of the Cr3C2 particles, and is more conducive to forming a uniform iron-based amorphous composite coating during the supersonic flame spraying process; moreover, the matching of the particle sizes of the two also improves the density and bonding strength of the iron-based amorphous composite coating, thereby improving the overall performance and durability of the iron-based amorphous composite coating.

[0052] In the present invention, the mixed powder is preferably dried before use, and the drying temperature is preferably 40-60°C, and in specific embodiments, it can be 40°C, 45°C, 50°C, 55°C or 60°C; the drying time is preferably 20-40 minutes, and in specific embodiments, it can be 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes. The present invention dries the mixed powder, which can significantly reduce its water content, thereby improving the fluidity of the mixed powder, which can not only improve the dispersibility of the mixed powder during the spraying process, but also reduce the particle agglomeration phenomenon caused by moisture. Good fluidity is the basis for achieving uniform coating and good adhesion, thereby ensuring the overall performance and durability of the coating.

[0053] In the present invention, the material of the metal substrate preferably includes 304 stainless steel, 316 stainless steel, aluminum alloy, nickel-based alloy or copper-based alloy; the nickel-based alloy preferably includes Inconel series nickel-based alloy. In the present invention, the metal substrate is preferably sandblasted and preheated before use. In the present invention, the metal substrate is preferably first cleaned, polished and second cleaned, and then sandblasted.

[0054] In the present invention, the solvent used in the first cleaning preferably includes acetone and / or ethanol, and the purpose of the cleaning is to remove grease and impurities.

[0055] In the present invention, the polishing is preferably performed using 60-600 mesh sandpaper. In a specific embodiment, 60 mesh, 120 mesh, 400 mesh and 600 mesh sandpaper can be used in sequence for polishing. The present invention polishes the surface of the metal substrate, which helps to improve the adhesion and surface quality of the iron-based amorphous composite coating. Among them, polishing with 60 mesh sandpaper can quickly remove the oxide layer and surface impurities; polishing with 120 mesh sandpaper can further flatten the surface, reduce roughness, and remove larger scratches; using 400 mesh sandpaper can remove minor defects and enhance surface smoothness; using 600 mesh sandpaper for fine polishing can effectively remove tiny particles and oxides to ensure uniform adhesion of the coating. Although polishing with 800 mesh and above can further improve smoothness, polishing with 600 mesh is sufficient to meet the requirements of coating adhesion. Therefore, reasonable polishing conditions are conducive to achieving a balance between coating performance and reducing process complexity to achieve optimal coating quality and efficiency.

[0056] In the present invention, the solvent used in the second cleaning preferably includes one or more of ethanol, methanol and isopropanol; the second cleaning is preferably ultrasonic cleaning; the frequency of the ultrasonic cleaning is preferably 20-40kHz, and in a specific embodiment, it can be 20kHz, 25kHz, 30kHz, 35kHz or 40kHz; the power of the ultrasonic cleaning is preferably 100-200W, and in a specific embodiment, it can be 100W, 120W, 140W, 150W, 160W, 180W or 200W. The present invention can produce sufficient cavitation effect by controlling the frequency range of ultrasonic cleaning to 20-40kHz, quickly form and collapse micro bubbles, thereby effectively removing dirt and impurities on the surface, and ensuring that the metal surface cleaning effect is optimal; while frequencies below 20kHz may cause excessive mechanical stress and damage the surface of the substrate, and frequencies above 40kHz may have a more delicate cleaning effect, but may not be sufficient to remove heavy dirt. Therefore, this frequency range achieves a good balance between cleaning effect and material safety. The present invention controls the power of ultrasonic cleaning to be within the range of 100 to 200 W, thereby ensuring the cavitation effect during the ultrasonic cleaning process and avoiding overheating or deformation of the substrate due to excessive power; by controlling the frequency and power range of ultrasonic cleaning, the cleaning effect can be significantly improved, ensuring that the surface of the metal substrate after cleaning meets the quality standards required for preparing the coating.

[0057] In the present invention, the process conditions of the sandblasting preferably include: the sandblasting medium is Al2O3, the particle size of the sandblasting medium is 50-120 mesh, and in a specific embodiment, it can be 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh, 110 mesh or 120 mesh; the sandblasting pressure is 0.2-0.6 MPa, and in a specific embodiment, it can be 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa or 0.6 MPa; the distance between the nozzle and the metal substrate is 150-300 mm, and in a specific embodiment, ... It can be 150mm, 160mm, 170mm, 180mm, 190mm, 200mm, 210mm, 220mm, 230mm, 240mm, 250mm, 260mm, 270mm, 280mm or 290mm, 300mm; the sandblasting time is 5 to 15min, and in a specific embodiment it can be 5min, 6min, 7min, 8min, 9min, 10min, 11min, 12min, 13min, 14min or 15min. The present invention adopts 50 to 120 mesh sandblasting media, which can achieve good cutting ability and appropriate surface roughness; by controlling the sandblasting pressure to 0.2 to 0.6MPa, it is beneficial to the uniformity of the sandblasting effect; by controlling the distance between the nozzle and the metal substrate to 150 to 300mm, it is beneficial to obtain an ideal sandblasting strength and covering effect; by controlling the surface roughness, it is helpful to enhance the adhesion between the iron-based amorphous composite coating and the metal substrate. The above parameters ensure the effectiveness of the sandblasting treatment and provide a good foundation for the subsequent supersonic flame spraying. The present invention can prevent the metal substrate from having excessive thermal expansion differences by sandblasting, and can improve the bonding strength between the iron-based amorphous composite coating and the metal substrate, thereby preventing the iron-based amorphous composite coating from peeling off or cracking.

[0058] In the present invention, the supersonic flame spraying is preferably completed within 30 minutes after the sandblasting is completed to avoid secondary oxidation or contamination of the metal substrate surface.

[0059] In the present invention, the temperature of the preheated metal substrate is preferably 150-250°C, and in specific embodiments, it can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C. The present invention controls the temperature after preheating to be 150-250°C, which helps to reduce the stress caused by the difference in thermal expansion coefficient between the substrate and the coating during supersonic flame spraying, thereby effectively improving the adhesion and density of the coating. And it can make the coating surface melt in a good state, reduce pore defects, and ultimately improve the comprehensive performance of the coating; too low temperature (below 150°C) may not effectively relieve the stress caused by the difference in thermal expansion; and too high temperature (above 250°C) may cause excessive thermal deformation of the metal substrate or a decrease in coating adhesion. Therefore, a preheating temperature of 150-250°C is an ideal choice, which is conducive to the optimization of coating quality and overall performance.

[0060] The present invention preferably adopts high velocity air fuel (HVAF) technology for supersonic flame spraying. HVAF technology utilizes high-speed air and fuel mixed gas to spray coating. Compared with traditional thermal spraying methods, the present invention adopts HVAF technology for supersonic flame spraying, which can achieve higher spraying speed and better coating density, thereby improving the overall mechanical properties and wear resistance of the iron-based amorphous composite coating.

[0061] In the present invention, the process conditions of the supersonic flame spraying preferably include: an oxygen flow rate of 1500 to 2200 SCFH, which can be 1500 SCFH, 1600 SCFH, 1700 SCFH, 1800 SCFH, 1900 SCFH, 2000 SCFH, 2100 SCFH or 2200 SCFH in a specific embodiment; a spraying distance of 250 to 350 mm, which can be 250 mm, 260 mm, 270 mm, 280 mm, 290 mm, 300 mm, 310 mm, 320 mm, 330 mm, 340 mm or 350 mm in a specific embodiment; a fuel flow rate of 5 to 8 GPH, which can be 5 GPH, 5.5 GPH, 6 GPH, 6.5 GPH in a specific embodiment. H, 7GPH, 7.5GPH or 8GPH; the fuel preferably includes one or more of kerosene, propylene, natural gas and liquefied petroleum gas; the powder delivery rate is 30-40g / min, and in specific embodiments it can be 30g / min, 31g / min, 32g / min, 33g / min, 34g / min, 35g / min, 36g / min, 37g / min, 38g / min, 39g / min or 40g / min; the carrier gas flow rate is 10-15L / min, and in specific embodiments it can be 10L / min, 11L / min, 12L / min, 13L / min, 14L / min or 15L / min; the carrier gas preferably includes nitrogen, argon, helium, air or hydrogen. In the present invention, the carrier gas is mainly used to provide the fluidity and aerodynamic force required for supersonic flame spraying; among them, nitrogen has a low cost; the low density and high thermal conductivity of helium help to improve the spraying speed and the density of the coating; argon can remain stable at high temperatures and can effectively prevent oxidation, thereby improving the quality of the coating, and its cost and density are between nitrogen and helium; air has a low cost and is easy to obtain, but in some applications it may cause oxidation of the coating, thereby affecting performance; although hydrogen has high thermal conductivity, due to its flammable and explosive properties, it must be used under strictly controlled conditions to ensure safety. Among the fuels used in the present invention, kerosene has a high combustion temperature and can provide sufficient heat to quickly heat the coating material to a molten state, which helps to improve the density and bonding strength of the coating, especially when preparing an iron-based amorphous composite coating, it can improve the high quality and good hardness, wear resistance and corrosion resistance of the coating; kerosene produces less oxides when it burns, and the oxidation phenomenon of the coating and the substrate will be reduced, thereby ensuring the purity and quality of the coating; kerosene has high volatility and good combustion efficiency, which can avoid overheating and deformation of the substrate, while ensuring the accuracy and density of the coating. Kerosene has high combustion efficiency and stable heat release, which makes the coating cool faster, thereby effectively reducing the pores and defects in the coating, further improving the density, hardness and corrosion resistance of the coating; and less pollutants are emitted during its combustion process.Propylene has a lower combustion temperature and higher combustion efficiency, which can improve the compactness of the coating, reduce the formation of pores in the coating, and improve hardness and wear resistance; the heat generated by natural gas during combustion is relatively stable, and after mixing with air, it has lower pollutant emissions; for fields with high requirements for coating quality, natural gas also helps to control oxidation reactions during spraying; liquefied petroleum gas has a higher calorific value and better volatility; it is often used in HVAF spraying to improve the spraying speed and increase the compactness of the coating, and liquefied petroleum gas performs better in temperature control and is suitable for large-scale coating preparation. The present invention performs supersonic flame spraying under the above conditions, which is conducive to improving the hardness, wear resistance and corrosion resistance of the iron-based amorphous composite coating.

[0062] After the supersonic flame spraying, the present invention preferably also includes polishing the formed iron-based amorphous composite coating after grinding to obtain an iron-based amorphous composite coating with a smooth surface. In the present invention, the grinding is preferably performed using 60 to 3000 mesh sandpaper for grinding. In a specific embodiment, 60 mesh, 120 mesh, 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 1500 mesh, 2000 mesh and 3000 mesh sandpaper can be used for grinding in sequence. The present invention is polished under the above conditions, and the rough layer and uneven parts can be removed, the grinding effect can be improved, and the quality of the iron-based amorphous composite coating can be improved. The present invention uses sandpaper from coarse to fine for grinding, which can effectively remove the defects on the surface of the iron-based amorphous composite coating and avoid excessive scratches at each stage. Among them, using 60-mesh and 120-mesh sandpaper for polishing can effectively remove larger defects, using 400-mesh and 600-mesh sandpaper for polishing can improve the smoothness and fineness of the surface, using 800-mesh and 1000-mesh sandpaper for detailed polishing to make the surface smoother, and using 1500-mesh, 2000-mesh and 3000-mesh sandpaper for polishing can achieve the final smooth effect, thereby achieving the ideal gloss. This step-by-step polishing method not only improves processing efficiency, but also significantly improves surface quality, providing better adhesion for subsequent painting or bonding.

[0063] The present invention also provides the use of the iron-based amorphous composite coating described in the above technical solution or the iron-based amorphous composite coating prepared by the preparation method described in the above technical solution as a protective layer. In the present invention, the iron-based amorphous composite coating is preferably used as a protective layer in the fields of electronics, materials, engineering, aerospace, energy, petrochemicals or oceans, and more preferably as a protective layer for pump and valve components.

[0064] Compared with amorphous alloys of other systems, the FeCrMo amorphous coating provided by the present invention has high hardness, high wear resistance and better corrosion resistance, and can resist the erosion of corrosive media such as acids and alkalis very well; the FeCrMo iron-based amorphous coating does not contain toxic substances, thereby avoiding serious pollution to the environment; the research on the FeCrMo iron-based amorphous coating has a low cost, and can simultaneously take into account the good mechanical properties of the metal matrix and the excellent properties of the amorphous alloy. Cr3C2 particles belong to ceramic particles and have excellent hardness, chemical stability and corrosion resistance. The present invention successfully improves the pore state of the coating cross section and surface by adding 3-10wt% of Cr3C2 particles as a reinforcing phase in the FeCrMo amorphous coating, with fewer pores and a denser internal structure, which significantly improves the hardness, wear resistance and corrosion resistance of the iron-based amorphous composite coating. The iron-based amorphous composite coating provided by the present invention is used as a protective layer to extend the service life of the metal substrate, especially the metal substrate under high load and harsh working conditions (such as pump valve components used in corrosive environments), and reduce the frequency of its maintenance and replacement.

[0065] The iron-based amorphous composite coating provided by the present invention is a corrosion-resistant coating, which shows excellent corrosion resistance in marine environments and other highly corrosive media, can effectively protect mechanical parts from corrosion damage, significantly extend the service life of equipment, reduce maintenance costs and downtime, and can be widely used in the fields of ships, offshore platforms and marine structures. Due to the high hardness of the iron-based amorphous composite coating and the uniform dispersion of Cr3C2 particles, the iron-based amorphous composite coating also shows excellent performance in wear resistance. The coating can significantly reduce the wear rate of mechanical parts under high friction and high pressure conditions, and is particularly suitable for key parts such as bearings and gears. The performance of the iron-based amorphous composite coating under high temperature conditions is also outstanding. Thanks to the strengthening effect of Cr3C2 particles, it can maintain good wear resistance and corrosion resistance at higher temperatures. Therefore, the coating has important application value in the surface protection of equipment such as gas turbines, heat exchangers and furnace walls in high temperature working environments. These applications not only require the coating to have high hardness, but also need to maintain its chemical stability and mechanical strength at extreme temperatures, further demonstrating the wide applicability and technical advantages of the coating.

[0066] In order to further illustrate the present invention, the iron-based amorphous composite coating provided by the present invention and its preparation method and application are described in detail below in combination with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0067] In the following examples and comparative examples, the chemical composition of the X8-FeCrMoCB amorphous powder is, by mass percentage, Cr25-27%, Mo 16-18%, C 2.0-2.5%, B 2.0-2.2%, Fe balance, and the particle size is 15-53 μm; Figure 1 The SEM image of X8-FeCrMoCB amorphous powder shows that the X8-FeCrMoCB amorphous powder has good sphericity. The particle size of Cr3C2 (ceramic particles) is 35-55 μm, and the purity is 99.1%. Figure 2 This is the SEM image of Cr3C2 particles. It can be seen from the figure that the Cr3C2 particles are spherical and the particle size is about 35 to 55 μm.

[0068] Example 1

[0069] The X8-FeCrMoCB amorphous powder and the Cr3C2 particles were dried at 50° C. for 30 minutes to obtain a mixed powder, wherein the mass content of the Cr3C2 particles was 3%.

[0070] A 304 stainless steel substrate (50 mm × 25 mm × 7.5 mm) was cleaned with acetone, polished with 60 mesh, 120 mesh, 400 mesh and 600 mesh sandpaper in sequence, ultrasonically cleaned with anhydrous ethanol at 20-40 kHz and 100-200 W, and sandblasted to obtain a sandblasted substrate, and the sandblasted substrate was preheated to 200° C. to obtain a preheated substrate. The process parameters of the sandblasting treatment are as follows: the sandblasting medium is 50-120 mesh Al2O3, the sandblasting pressure is 0.2-0.6 MPa, the sandblasting distance is 150-300 mm, the sandblasting time is 5-15 min, and the surface roughness (Ra) of the sandblasted substrate is 1.0-3.0 μm.

[0071] The mixed powder is used to form an amorphous composite coating by supersonic flame spraying on the preheated substrate surface. The process parameters of supersonic flame spraying are: HVAF technology is used for supersonic flame spraying, oxygen flow rate is 1850SCFH, spraying distance is 300mm, kerosene flow rate is 6.5GPH, powder feeding rate is 35g / min, and carrier gas N2 flow rate is 13L / min.

[0072] Figure 3 This is a physical picture of the amorphous composite coating prepared in Example 1 before grinding and polishing. It can be seen from the figure that the surface of the coating is uniform gray. Since it has not undergone subsequent grinding treatment, the surface retains the natural texture of the spraying process. Overall, the coating exhibits excellent uniformity and complete coverage. The coating surface presents a relatively rough feature, and no obvious cracks or peeling are observed, indicating that the spraying process has high stability and strong coating adhesion, and can provide reliable surface protection performance in practical applications.

[0073] The substrate containing the amorphous composite coating was cut into blocks of 12.5 mm × 12.5 mm × 7.5 mm, and the surface and cross section of the iron-based amorphous composite coating were polished using 60 mesh, 120 mesh, 400 mesh, 600 mesh, 800 mesh, 1000 mesh, 1500 mesh, 2000 mesh and 3000 mesh sandpaper in sequence, and then polished to facilitate subsequent microstructural analysis, performance evaluation and electrochemical testing.

[0074] Embodiments 2 to 4

[0075] The iron-based amorphous composite coating was prepared according to the method of Example 1, the only difference from Example 1 being that the mass contents of Cr3C2 particles in the mixed powder were 4.5%, 6% and 7.5% respectively.

[0076] Comparative Example 1

[0077] The FeCrMo iron-based amorphous composite coating was prepared according to the method of Example 1, the only difference from Example 1 being that the mixed powder was replaced with X8-FeCrMoCB amorphous powder, and the mass content of Cr3C2 particles was 0%.

[0078] Test Example 1

[0079] The material structure and mechanical properties of the iron-based amorphous composite coatings prepared in Examples 1 to 4 and Comparative Example 1 were analyzed and tested.

[0080] (1) Organizational structure analysis test

[0081] (1.1) X-ray diffractometer analysis (XRD)

[0082] Figure 4 XRD patterns of amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4. In the range of 35 to 40°, the coatings show diffuse scattering peaks unique to the amorphous phase, indicating that the coatings with different Cr3C2 particle contents are mainly amorphous structures; PDF card comparison revealed that the diffraction peaks of Cr3C2 and Fe3C are superimposed on the amorphous peaks. The appearance of Fe3C may be due to the small amount of crystallization of the amorphous phase caused by high temperature and high pressure during supersonic flame spraying; further calculations show that the amorphous rates of the amorphous coatings with mass fractions of 3%, 4.5%, 6% and 7.5% Cr3C2 ceramic particles are 76.81%, 75.45%, 74.23% and 70.75%, respectively.

[0083] (1.2) Scanning electron microscopy analysis (SEM)

[0084] Figure 5The SEM images of the polished upper surfaces of the amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4, where a has a content of 3%, b has a content of 4.5%, c has a content of 6%, and d has a content of 7.5%. As can be seen from the figure, as the content of the added Cr3C2 particles gradually increases from 3% to 6%, the number of pores in the coating shows a trend of gradually decreasing, but when the particle content reaches 7.5%, the number of pores in the coating increases slightly. This may be because when the addition of Cr3C2 particles gradually increases from 3% to 6%, after sufficient mixing before spraying, the Cr3C2 particles can be evenly distributed in the coating alloy powder, making it easier for the Cr3C2 particles to fill the pores during the coating spraying process, reducing the formation of pores; when the addition amount reaches 7.5%, too many Cr3C2 particles may cause accumulation between the particles, resulting in an increase in the pores in the coating; in addition, due to the high melting point of Cr3C2 particles, excessive Cr3C2 particle content will also increase the melting point of the alloy powder, resulting in its melt fluidity becoming poor during the spraying process, making it difficult for the Cr3C2 particles to fully fill the pores, and ultimately leading to an increase in the number of pores in the coating.

[0085] Figure 6 The cross-sectional SEM images of amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4, where (a) has a content of 3%, (b) has a content of 4.5%, (c) has a content of 6%, and (d) has a content of 7.5%. The thickness of all coatings is maintained between 200 and 400 μm. As can be seen from the figure, the bonding between all coatings and the 304 stainless steel substrate is relatively good, and no cracking between the coating and the substrate occurs, which indicates that the prepared amorphous composite coatings with different particle contents have excellent performance in structural integrity and coating-substrate bonding, providing a good foundation for future applications in mechanical properties and corrosion resistance.

[0086] (1.3) Characterization of coating microstructure - morphological changes of pores and particles and element distribution analysis (BSE and EDS)

[0087] Figure 7 BSE image (a) and EDS images (b~g) of the pores in the amorphous composite coating (Cr3C2 content is 7.5%) prepared in Example 4. The black positions are pores. After EDS element analysis of the coating surface, it was found that the pore area was mainly composed of O and C elements.

[0088] Figure 8BSE image (a) and EDS image (b-g) of Cr3C2 particles in the amorphous composite coating (Cr3C2 content of 7.5%) prepared in Example 4. It can be seen from the EDS image that the white area gathers higher concentrations of Cr and C elements, indicating that these areas are mainly composed of Cr3C2 particles. The gray area is mainly composed of other elements of the coating. More importantly, the image analysis reveals that during the spraying process, the morphology of the Cr3C2 particles has changed significantly, gradually splitting from the original large particles into multiple smaller particles, which can be clearly observed in the image. Analysis of the cause of this change may be related to the high temperature and high pressure environment of supersonic flame spraying. During the spraying process, under the action of strong airflow and thermal energy, the morphology of the Cr3C2 particles split, which may be due to the difference in thermal expansion between the particles and the stress caused by particle collision during the spraying process, resulting in the cracking and dispersion of the originally larger Cr3C2 particles. This phenomenon may have a certain impact on the overall structure and properties of the coating, especially on the mechanical properties and corrosion resistance of the coating.

[0089] according to Figure 7 and Figure 8 The results of elemental analysis show that the aggregation of O and C elements is found in the pores of the coating. This is because the unique structure of the pores provides more surface area for oxidation, thereby increasing the possibility of oxidation. Especially during the supersonic flame spraying process, the high temperature, high pressure and oxygen-rich atmosphere may trigger an oxidation reaction on the coating surface, leading to the aggregation of oxygen elements. In particular, there is a difference in oxygen concentration in the pores during the spraying process. This difference may cause the oxidation reaction around the pores to be more intense.

[0090] (2) Mechanical properties test

[0091] Mechanical property tests are crucial in the study of Fe-based amorphous composite coatings with different Cr3C2 particle contents. Through these tests, the effect of Cr3C2 particle content on coating strength, hardness, toughness and wear resistance can be evaluated. These data help determine the optimal particle content, thereby optimizing the overall performance of the coating and improving its durability and reliability in practical applications. Systematic testing and analysis provide a scientific basis for improving coating design and enhancing application performance.

[0092] (2.1) Hardness test

[0093] The microhardness of the cross-section of the 304 stainless steel substrate and its iron-based amorphous composite coating was measured using a HV-1000 Vickers microhardness tester. During the test, the applied load was 0.05 kg and the holding time was 15 seconds. During the test, a measuring point was set every 50 μm in the parallel and vertical directions at the interface between the coating and the substrate. Each set of measurements contained five data points, and at least three sets of measurements were performed. Finally, the average value of the three sets of data was taken as the microhardness value of the coating and the 304 stainless steel substrate.

[0094] Fig. 9 The microhardness diagram of the amorphous composite coating with different Cr3C2 contents prepared in Examples 1 to 4. As can be seen from the figure, the average hardness of the amorphous composite coating is about two to three times that of the 304 stainless steel substrate. This phenomenon is mainly attributed to the unique advantages of amorphous alloys. Due to the long-range disorder of amorphous alloys, it is not easy to slip when subjected to force, so it shows a higher hardness than the substrate; as the Cr3C2 particle content increases from 3% to 6%, the hardness of the coating shows an overall upward trend, however, when the particle content continues to increase to 7.5%, the hardness of the coating begins to decrease, and when the Cr3C2 particle content is 6%, the microhardness of the coating reaches a maximum value of 962.7HV. The reason for this change is that the hardness of the coating is mainly affected by the porosity, and the pores will cause local stress concentration inside the material, thereby reducing the overall hardness, especially when subjected to external stress, the pores may become the initiation point of cracks, further reducing the hardness of the material.

[0095] The hardness change trend of the joint is that when the particle content increases from 3% to 6%, the hardness of the joint also shows an upward trend, and then begins to decrease. When the Cr3C2 particle content is 6%, the microhardness of the joint reaches a maximum value of 532.4HV; the occurrence of this phenomenon is directly related to the bonding quality of the above-mentioned coating and substrate. The better the bonding quality, the less likely stress concentration will occur, thereby achieving a higher hardness; in general, the microhardness of the joint is about 500HV, which is also higher than the microhardness of 304 stainless steel (about 300HV).

[0096] In addition, the hardness of the 304 stainless steel substrate within 50 microns near the joint is also slightly improved. This phenomenon is mainly attributed to the influence of high temperature on the microstructure of the substrate surface during the spraying process. High temperature treatment may lead to grain refinement on the substrate surface and induce local phase transformation (such as ferrite or martensite transformation). These phase transformations usually significantly change the crystal structure of the substrate, thereby improving the hardness and mechanical properties of this area to a certain extent.

[0097] (2.2) Friction and wear test

[0098] The friction and wear conditions were tested using an MSR-2T electrochemical reciprocating friction and wear tester. Before the measurement, the amorphous composite coating was inlaid with polyethylene resin, and an MSR-2T electrochemical reciprocating friction and wear tester was used. This device simulates the friction and wear under actual working conditions by performing high-frequency reciprocating friction between the coating and the friction pair; the experimental parameters were set as a load of 6N, a friction path of 5mm, a speed of 270r / min, a wear time of 24min, and the friction pair was an Al2O3 ceramic ball with a diameter of 3mm; after the experiment, the sample was ultrasonically cleaned with ethanol, and observed and analyzed by confocal microscopy and SEM. Subsequently, a CHOTEST model white light interferometer was used to measure the surface of the worn coating. The white light interferometer can accurately depict the microscopic morphology, wear state and deformation characteristics of the material surface after the friction and wear experiment, and calculate the wear amount based on the change in the coating mass loss before and after the friction and wear experiment.

[0099] Fig.10 The friction coefficient of the amorphous composite coating with different Cr3C2 contents prepared in Examples 1 to 4 varies with time. As can be seen from the figure, the friction coefficient of the coatings with different Cr3C2 particle contents has a similar variation trend. This is because there is point contact friction in the early stage of friction. The contact area of ​​point contact friction is small, the local pressure is large, and the friction coefficient is on the rise. Then, the point contact transitions to surface contact. Compared with point contact friction, the contact surface gradually increases, the pressure distribution is more uniform, the friction process also enters a stable stage, and the friction coefficient also tends to be stable.

[0100] The average friction coefficient of the coating with a Cr3C2 particle content of 3% is 0.6906, the friction coefficient of the coating with a Cr3C2 particle content of 4.5% is reduced to 0.5543, and the friction coefficient of the coating with a Cr3C2 particle content of 6% is significantly reduced to 0.2933, while the friction coefficient of the coating with a Cr3C2 particle content of 7.5% increases again to 0.4449; Generally speaking, a lower friction coefficient reflects better wear resistance, because the friction coefficient directly affects the magnitude of the friction force exerted on the surface when in contact. The smaller the friction coefficient, the smaller the friction force. Smaller friction can reduce surface wear and damage, thereby improving the wear resistance of the coating. However, the friction coefficient is not the only indicator that reflects the wear resistance of the coating, so the wear quality of the coating was also measured and analyzed.

[0101] Fig.11The wear mass diagram of the amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4. As can be seen from the figure, under the same friction and wear conditions, the coating with a Cr3C2 particle content of 3% shows the largest wear mass, which is about 0.153g, while the coating with a Cr3C2 particle content of 4.5% slightly decreases to about 0.144g. With the increase of the Cr3C2 particle content, the wear mass of the coatings with Cr3C2 particle contents of 6% and 7.5% decreases to about 0.123g and 0.132g respectively; through the comparison of the wear mass, it can be concluded that the amorphous composite coating with a Cr3C2 particle content of 6% has the best wear resistance under the same friction conditions.

[0102] Fig.12 The microstructure diagrams of amorphous composite coatings with different Cr3C2 contents prepared in Examples 1 to 4 after wear, among which (a) has a content of 3%, (b) has a content of 4.5%, (c) has a content of 6%, and (d) has a content of 7.5%. As can be seen from the figure, after the friction and wear experiment, areas with no obvious changes, rough areas, and bright particles appeared on the coating surface. This phenomenon is mainly caused by the strong friction of the Al2O3 ceramic ball of the friction pair. During the friction and wear process, the coating is subjected to great mechanical stress. Due to some inevitable defects in thermal spraying, stress concentration will occur locally. The pre-polished smooth coating surface may become no longer smooth during the friction process, and may even peel off until the substrate surface is exposed. High-frequency contact and local stress concentration cause dynamic changes on the coating surface. The formation of bright particles mainly originates from the friction process. When the friction pair wears back and forth on the coating, the extrusion effect promotes the generation of these particles. These bright particles indicate that the material has undergone local plastic deformation. The stress concentration in the extrusion area also affects the service life of the coating. In subsequent use, there will be more serious stress concentration, which will reduce the service life of the coating. In contrast, the rough area has more stress concentration points due to surface irregularities and defects, which leads to more serious stress concentration and makes these areas bear greater stress. In areas where no obvious changes occur, the stress concentration is lighter, the mechanical stress is smaller, and the surface state is relatively good. Although bright particles can also cause significant stress concentration, the number of concentration points is smaller, and the stress concentration effect is relatively lighter than that of rough areas. Therefore, the fewer bright particles and rough areas observed by SEM, the better the wear resistance of the coating is generally.

[0103] Fig.13The EDS element analysis results of the surface characteristic areas of the iron-based amorphous composite coating prepared in Example 4. It can be seen from the figure that in the rough area and the bright particles, the carbon element shows a significant aggregation phenomenon. Especially under high stress conditions, the local area will produce a higher temperature due to stress concentration and friction heat accumulation during friction or wear. In this high temperature environment, the diffusion of carbon is significantly enhanced, thereby promoting the aggregation of carbon elements in high stress and high temperature areas (such as extrusion areas and rough areas), and the concentration of carbon elements in these areas is relatively high; as mentioned above, bright particles appear in areas that have undergone local plastic deformation, and their strong reflective properties make these particles appear high brightness in SEM images. This phenomenon is closely related to the surface morphology. The raised surface area can reflect more secondary electrons, so it shows a strong brightness. When analyzing the microscopic morphology of the worn area, although SEM can provide certain information, SEM images alone are not sufficient to fully evaluate the surface changes after wear. In order to deeply understand the changes in surface morphology during wear, the measurement of the worn surface profile combined with the laser confocal microscope white light interferometer can provide more accurate three-dimensional surface data. This analysis method that combines SEM with interferometry technology is very helpful in revealing the microscopic mechanism of coating wear and provides a more scientific basis for further optimizing the wear resistance of the coating.

[0104] Fig.14 The surface profiles of amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 after friction and wear, obtained using a laser confocal microscope and white light interferometer, are (a) 3%, (b) 4.5%, (c) 6%, and (d) 7.5%. As can be seen from the figure, the surface wear marks of the iron-based amorphous composite coating with a Cr3C2 particle content of 6% are shallower and narrower than those of the coatings with other contents, indicating that it has undergone a relatively mild wear process; in contrast, the wear marks on the surface of the composite coating with a Cr3C2 particle content of 3% are deeper and wider, indicating that it has undergone more significant wear.

[0105] In summary, the present invention successfully prepared amorphous composite coatings with different Cr3C2 particle contents by supersonic flame spraying technology under a series of fixed process parameters, and studied and analyzed the porosity state, microstructure and microhardness of coatings with different Cr3C2 particle contents. At the same time, the influence mechanism of Cr3C2 particles on the hardness and porosity state of the coating was analyzed, and the following conclusions were drawn:

[0106] (1) The iron-based amorphous composite coatings with different Cr3C2 particle contents prepared by HVOF have good surface melting state, a small amount of pores, and a relatively dense internal structure. They contain both Cr3C2 phase and Fe3C phase, and the amorphous ratio is above 70%.

[0107] (2) By adding Cr3C2 particles, the porosity of the coating cross section and surface was successfully improved. When the amount of Cr3C2 particles added increased to 6%, the number of pores on the coating surface first decreased, but when the amount of Cr3C2 particles added increased to 7.5%, the number of pores increased instead.

[0108] (3) The presence of Cr3C2 particles increases the hardness of the coating. When the addition amount of Cr3C2 particles is 6%, the microhardness of the coating is the highest, about 962.7HV, which is about 3 times the hardness of the 304 stainless steel substrate, and the hardness of the joint is about 500HV.

[0109] (4) The wear morphology of the coating is mainly composed of two areas: a rough peeling area and a relatively smooth area. In the friction and wear experiment, it was found that when the content of Cr3C2 particles in the coating reached 6%, the peeling phenomenon was significantly reduced. The coating with a content of 6% Cr3C2 particles showed the best wear resistance.

[0110] Test Example 2

[0111] Electrochemical performance test of Fe-based amorphous composite coating and FeCrMo iron-based amorphous composite coating prepared in comparative example 1

[0112] The corrosion behavior of amorphous composite coatings containing different contents of Cr3C2 particles in simulated seawater was analyzed through electrochemical tests and immersion experiments. At the same time, the corrosion protection performance of these coatings on 304 stainless steel was detected and evaluated. The corrosion mechanism of the coating in simulated seawater was explored by characterizing the surface products of the coating after immersion.

[0113] (1) Electrochemical experiments

[0114] The CS350M electrochemical workstation was used to evaluate the corrosion resistance of the iron-based amorphous composite coating in simulated seawater. The experiment adopted a standard three-electrode system, in which the Ag / AgCl electrode was used as the reference electrode, the platinum electrode was used as the auxiliary electrode, and the working electrode was the iron-based amorphous composite coating. The corrosive solution was simulated seawater at room temperature, and the simulated seawater composition was: NaCl 24.420 g / L, MgCl 2 5.16 g / L, Na 2 SO 4 4.002 g / L, CaCl 2 1.017 g / L, and KCl 0.693 g / L.

[0115] The test process is as follows: first, the open circuit potential (OCP) is measured, the sample is immersed in simulated seawater for 1800s, and after the open circuit potential is stable, the electrochemical impedance spectroscopy test is performed. The electrochemical impedance spectroscopy test covers a frequency range of 10 -2 ~10 5Hz, the amplitude of the sine wave disturbance was 10mV (relative to the open circuit potential), and then the potentiodynamic polarization test was performed, the potential scanning range was -1V to 1V, and the scanning rate was 0.5mV / s. The electrochemical impedance spectroscopy data were fitted and analyzed by the CS studio 6 software that comes with the CS350M electrochemical workstation, and the polarization curves were processed using the Tafel linear extrapolation method.

[0116] (1.1) Open circuit potential test analysis

[0117] In order to study the corrosion resistance of iron-based amorphous composite coatings with different Cr3C2 particle contents, the corrosion resistance of the coatings was analyzed and compared. Amorphous composite coatings with different Cr3C2 particle contents were immersed in simulated seawater for 1800s, and the open circuit potential (OCP) curves of different amorphous composite coatings were measured by electrochemical workstation.

[0118] Fig.15 The OCP curves of amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4. The results show that the open circuit potential of the coating with 6% Cr3C2 particle content is greater than that of the coating with 7.5% Cr3C2 particle content, followed by 4.5% and 3%. The higher the open circuit potential, the smaller the corrosion tendency of the coating. This is because a high open circuit potential means that the charge transfer in the system is relatively difficult, the charge transfer reaction is relatively slow, and it has stronger electrochemical stability. The OCP curve only provides static information of the open circuit potential and cannot fully represent the corrosion resistance of the coating. The OCP curve can only preliminarily determine, predict and evaluate the corrosion resistance of the coating. The corrosion resistance of the coating is also affected by other factors, such as the composition, structure and bonding strength of the coating, so it is necessary to perform potentiodynamic polarization test and impedance test.

[0119] (1.2) Potentiodynamic polarization test analysis

[0120] Fig.16 Polarization curves of iron-based amorphous composite coatings with different Cr3C2 particle contents (0%, 3%, 4.5%, 6% and 7.5%) prepared in Examples 1 to 4 and Comparative Example 1. The self-corrosion current density (Icorr) and self-corrosion potential (Ecorr) of the amorphous composite coatings with different Cr3C2 particle contents were obtained by Tafel linear extrapolation method. The relevant data are shown in Table 1.

[0121] Table 1 Polarization curve fitting parameters of Fe-based amorphous composite coatings with different Cr3C2 particle contents

[0122] Depend on Fig.16As shown in Table 1, the self-corrosion current density of the coating is basically stable at around 100 at different particle contents, without significant changes; in contrast, the self-corrosion potential shows different trends: the self-corrosion potential of the coating with 6% Cr3C2 particle content is greater than that of the coating with 7.5% Cr3C2 particle content, followed by 4.5% and 3%, which indicates that in simulated seawater, the coating with 6% Cr3C2 particle content has the smallest corrosion tendency and the best corrosion resistance.

[0123] This is because the self-corrosion potential reflects the potential when the coating reaches equilibrium with its electrochemical system. A high self-corrosion potential indicates that the coating is more inclined to be in a more stable state. A high self-corrosion potential means that it is easier to form a stable oxide film or other protective layer on the coating surface, which can slow down the erosion of the corrosive medium on the material, thereby reducing the corrosion rate. On the other hand, a high self-corrosion potential also means that the electrochemical reaction rate of the coating is slower, the electron transfer and ion transport reactions are relatively less, and the corrosion tendency is smaller. That is, in a corrosive environment, the coating can maintain the minimum corrosion tendency and the best corrosion resistance.

[0124] (1.3) Electrochemical impedance spectroscopy test analysis

[0125] Electrochemical impedance spectroscopy (EIS) is a commonly used analytical method in the study of chemical corrosion failure of coatings. It is as important as potentiodynamic polarization test analysis. -2 Hz to 10 -5 The EIS test results are obtained by performing a sinusoidal wave perturbation with an amplitude of 10mV in the frequency range of Hz. Through EIS, the response data of the electrochemical system to the electrical signal, such as the impedance modulus and phase angle, can be obtained. Among them, the Nyquist plot is widely used to visualize EIS data. The Nyquist plot can intuitively display the EIS data on a plane, thereby presenting the response characteristics of the impedance.

[0126] In the Nyquist plot, the radius of the capacitor arc is considered to be an important metric feature to characterize the corrosion resistance of the material. A larger capacitor arc radius means better corrosion resistance, because the increase in the capacitor arc radius represents an increase in the charge transfer resistance of the electrochemical system, which slows down the electrochemical reaction and improves the stability of the electrochemical system, thereby reflecting the better corrosion resistance of the coating.

[0127] Fig.17Nyquist plots and schematic diagrams of coating equivalent circuits (inset) for amorphous composite coatings with different Cr3C2 particle contents (0%, 3%, 4.5%, 6% and 7.5%) prepared for Examples 1 to 4 and Comparative Example 1. In the Nyquist plot, the horizontal axis Z' (real impedance) reflects the resistive behavior of the electrochemical system, which is mainly related to the conductivity of the coating and the stability of the interfacial reaction. The larger the Z' value, the greater the resistance encountered when the current flows in the system, which in turn indicates the resistive characteristics of the coating; the vertical axis Z" (imaginary impedance) reflects the reactive behavior of the system, reflecting the charge transfer and energy storage characteristics. A larger Z" value usually means a stronger charge transfer resistance or a significant capacitance effect, revealing the electrochemical reaction kinetics of the coating; through a comprehensive analysis of the real and imaginary impedances, the corrosion resistance of the coating and its electrochemical stability can be effectively evaluated. In addition, the experimental results show that the coating containing 6% Cr3C2 particles has a larger capacitance arc radius, which is better than the coating containing 7.5% Cr3C2 particles, which exhibits a lower capacitance arc radius. The other coatings containing 4.5% and 3% Cr3C2 particles also showed a similar trend, which was highly consistent with the results of potentiodynamic polarization test and open circuit potential test, further verifying the effect of different Cr3C2 particle contents on the electrochemical properties of the coatings.

[0128] In order to deeply analyze the EIS experimental data, the coating impedance spectrum was fitted and an equivalent circuit based on the actual physical model was designed. In this simulation circuit, R1 represents the resistance of simulated seawater, R2 represents the resistance of charge transfer, and CPE represents the capacitance between pores and cracks and simulated seawater. The results are shown in Table 2.

[0129] Table 2 Fitting results of components in the equivalent circuit

[0130]

[0131]

[0132] It can be found from Table 2 that during the experiment, the solution resistance R1 varies within a range of about 10, with little fluctuation, which indicates that the simulated seawater solution conditions are relatively stable during the test. In addition, the value of the resistance R2 reflects the resistance to charge transfer on the sample surface. The coating with a 6% Cr3C2 particle content exhibits the largest R2 value, indicating that the electrochemical system of the coating has the most significant charge transfer resistance. The introduction of Cr3C2 particles effectively inhibits the progress of the electrochemical reaction and enhances the stability of the electrochemical system, thereby significantly improving the corrosion resistance of the coating.

[0133] By simulating seawater as the electrolyte, the coatings with different Cr3C2 particle contents were subjected to open circuit potential test, potentiodynamic polarization test and electrochemical impedance spectroscopy test at room temperature. The three test results all showed that the coating with 6% Cr3C2 particle content showed the best corrosion resistance, which was attributed to the low porosity of the coating. According to the EDS analysis results in Test Example 1, oxygen elements had already accumulated around the pores of the coating during the spraying process, which means that these pore areas had been partially oxidized during spraying. The areas that were oxidized first became the core of corrosion because they had partially lost their original amorphous structure, weakening their protective properties. Therefore, electrochemical reactions usually occurred preferentially in these oxidized areas. , forming the core of coating corrosion; in addition, in the simulated seawater environment, oxidation reaction is one of the main processes of metal corrosion. The special structure of the pores provides more surface area, which in turn increases the site of oxidation reaction. The small potential difference formed inside and outside the pores will trigger local electrochemical reactions, which usually occur first in the pores and their surroundings to form corrosion cores. Once the corrosion core is formed in the pores and their surroundings, if it is long-term corrosion, the corrosion products produced will diffuse and aggregate in the pores and their surroundings. The generated oxide corrosion products will aggravate local corrosion, which will not only weaken the protective performance of the coating, but may also cause acidification or alkalization of the local environment, further aggravating the overall corrosion process. The accumulation of these corrosion products will weaken the mechanical strength and protective ability of the coating, leading to cracking and peeling.

[0134] (2) Immersion test

[0135] The surface of the pump and valve is likely to be in a seawater environment for a long time and is susceptible to long-term corrosion. Therefore, studying the long-term corrosion under simulated seawater conditions can help engineers better understand the corrosion resistance of the material, and hopefully help with material selection and the design of protective measures.

[0136] Before testing, the amorphous composite coatings were mounted with polyethylene resin to ensure that only the coating portion was in contact with the simulated seawater. Fig.18 The schematic diagram of the packaging of the amorphous composite coating sample. The amorphous composite coating was immersed in simulated seawater for 1 day, 7 days and 15 days. The simulated seawater was replaced every day. The samples immersed for 15 days were electrochemically tested to evaluate their corrosion performance.

[0137] The coating area and simulated seawater are 1 cm 2 :50mL was immersed in simulated seawater and placed in a constant temperature water bath at room temperature for immersion experiments. Coating samples with different Cr3C2 particle contents were used as comparisons.

[0138] (2.1) Weightlessness test

[0139] Before each coating is immersed, the test surface must be ground and polished, and then ultrasonically cleaned with anhydrous ethanol to remove impurities on the coating surface. During the immersion process, the simulated seawater is replaced every 24 hours. After being taken out, it is ultrasonically cleaned in a chromic acid solution for 15 minutes, then cleaned with anhydrous ethanol, and quickly dried with a hair dryer before a weight loss test is carried out.

[0140] Fig.19 The weight loss statistics of amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 after immersion for 15 days show that when the immersion time reaches 15 days, the coating containing 6% Cr3C2 particles has a minimum weight loss of 5.2 mg, which is lower than that of coatings with other particle contents. Specifically, the coating with 7.5% Cr3C2 particle content is second, followed by 4.5% and 3% coatings. According to the analysis of porosity in Test Example 1, the coating with 6% Cr3C2 particle content has the lowest porosity, which may be one of the important factors for its smaller weight loss and better corrosion resistance. Lower porosity means fewer pores inside the coating, making it difficult for seawater to penetrate into the lower layer of the coating, reducing the chance of corrosion. In contrast, coatings with higher porosity may be more easily invaded by seawater, resulting in more serious corrosion.

[0141] (2.2) Corrosion morphology analysis after long-term corrosion

[0142] In order to better observe the microscopic corrosion changes of amorphous composite coatings with different Cr3C2 particle contents after immersion in simulated seawater for 15 days, the coatings were immersed in simulated seawater for 1 day, 7 days and 15 days, and their microscopic surface morphologies were photographed with SEM.

[0143] Fig. 20SEM images of amorphous composite coatings with different Cr3C2 particle contents prepared in Examples 1 to 4 after immersion for 1 day, 7 days and 15 days, and SEM images after removal of corrosion products; a1, b1, c1, d1 are immersion for 1 day, and the particle contents are 3%, 4.5%, 6%, 7.5% respectively; a2, b2, c2, d2 are immersion for 7 days, and the particle contents are 3%, 4.5%, 6%, 7.5% respectively; a3, b3, c3, d3 are immersion for 15 days, and the particle contents are 3%, 4.5%, 6%, 7.5% respectively; a4, b4, c4, d4 are immersion for 15 days to remove corrosion products, and the particle contents are 3%, 4.5%, 6%, 7.5% respectively. As can be seen from the figure, after immersion for 1 day, the coating surface remained flat and basically unchanged; after immersion for 7 days, a small amount of pitting pits appeared on the coating surface, but no obvious corrosion products were seen. The formation of these pitting pits was mainly due to the local corrosion of simulated seawater, and the absence of corrosion products may be due to the short time, resulting in the corrosion products not beginning to accumulate on the surface; after immersion for 15 days, the corrosion products generated were granular and aggregated together. The formation of this granular corrosion product is due to the fact that during the point chemical reaction, the corrosion products are gradually deposited on the surface and form uneven precipitation over time, and these precipitations eventually crystallize into granular form.

[0144] In order to study the corrosion morphology more deeply, 180g / L chromic acid solution and coatings with different Cr3C2 particle contents were mixed in a beaker and cleaned with an ultrasonic cleaner to better remove corrosion products. As can be seen from the figure, as the immersion time reaches the 15th day, it can be observed that the pit area gradually increases and expands to the surrounding area, showing obvious pits and deeper pores; this phenomenon is consistent with the analysis results in Section 2.1, indicating that the aggregation of corrosion products will intensify the corrosion process.

[0145] (2.3) Corrosion product analysis

[0146] SEM observations showed that a thin layer of corrosion products covered the surface of the coating after the coating was immersed in simulated seawater for 15 days, and these corrosion products were analyzed by EDS. Fig.21The EDS image of the corrosion products in the amorphous composite coating (Cr3C2 content 7.5%) prepared in Example 4 shows that the corrosion products are mainly iron oxides. The corrosion products are mainly concentrated in the area with low chromium content, and less in the area with high chromium content. This is due to the excellent corrosion resistance of chromium. It can form a stable passivation film on the metal surface, thereby effectively preventing further corrosion. In addition, the chemical stability of chromium carbide makes it perform well in the simulated seawater environment, and it is not easy to have significant chemical reactions, so it has strong resistance to chloride ion corrosion. Similarly, the corrosion products mainly appear in the area with low molybdenum content, and less in the area with high molybdenum content. This is because molybdenum also has strong corrosion resistance, especially in chloride environment, it can significantly improve the corrosion resistance of iron-based alloys. In the area with high molybdenum content, the presence of molybdenum effectively prevents the invasion of corrosive media, thereby reducing the generation of corrosion products.

[0147] It should be pointed out that Cr3C2 particles did not show significant corrosion behavior during the corrosion process, and their improvement in corrosion resistance mainly came from improving the microstructure of the coating. As the content of Cr3C2 particles increased, the pores on the coating surface decreased, which effectively reduced the penetration of the corrosive medium and enhanced the overall corrosion resistance. Therefore, the corrosion resistance of the coating not only depends on the chemical stability of the particles, but is also closely related to the particle distribution and the microstructure of the coating.

[0148] Through EDS analysis of the corrosion products, it can be found that the corrosion products are mainly composed of iron and oxygen elements. In order to further determine the specific composition of the corrosion products, XRD analysis is performed on the samples. Fig. 22 From the XRD image of the amorphous composite coating (Cr3C2 content 7.5%) prepared in Example 4 after corrosion in simulated seawater, it can be found that the sample has the diffraction peak of Fe2O3, which indicates that in the simulated seawater environment, the iron-based amorphous alloy coating underwent an oxidation reaction, and Fe2O3 was the main corrosion product, while other corrosion products were not clearly shown in the XRD spectrum.

[0149] (2.4) Potentiodynamic polarization test analysis after long-term corrosion

[0150] In order to further explore the performance of the two composite coatings during the corrosion failure process, a 15-day full immersion experiment was conducted in a simulated seawater environment. The polarization curves of the coatings with different particle contents were measured by an electrochemical workstation, and the corrosion process of the coatings was further explained with the help of AC impedance spectroscopy analysis; it should be noted that open circuit voltage testing is usually not performed after corrosion. As mentioned above, open circuit voltage can only preliminarily predict and evaluate the corrosion resistance of the coating. Once the metal corrodes, the corrosion products will change the chemical properties and electrochemical behavior of the metal surface, which is likely to interfere with the open circuit voltage test results, thereby affecting the accuracy and reliability of the test, resulting in inaccurate test results that cannot truly reflect the actual situation.

[0151] Fig.23 Polarization curves of amorphous composite coatings with different Cr3C2 particle contents (0%, 3%, 4.5%, 6% and 7.5%) prepared in Examples 1 to 4 and Comparative Example 1 after immersion for 15 days. The self-corrosion current density (Icorr) and self-corrosion potential (Ecorr) of coatings with different Cr3C2 particle contents were obtained by Tafel extrapolation method. The relevant data are shown in Table 3.

[0152] Table 3 Polarization curve fitting parameters of amorphous composite coatings with different Cr3C2 particle contents after immersion for 15 days

[0153] Depend on Fig.23 As can be seen from Table 3, the self-corrosion current density of the coatings with different Cr3C2 particle contents is basically stable at around 100, without significant changes. In addition, the self-corrosion potential has a basically consistent trend before and after 15 days of immersion. According to Tables 1 and 3, after 15 days of immersion, the self-corrosion potential has decreased, but the self-corrosion potential of the coating with 6% Cr3C2 particle content is still the highest, showing the smallest corrosion tendency and the best corrosion resistance.

[0154] (2.5) Impedance spectrum test analysis after long-term corrosion

[0155] Fig.24 The Nyquist plots of amorphous composite coatings with different Cr3C2 particle contents (0%, 3%, 4.5%, 6% and 7.5%) prepared in Examples 1 to 4 and Comparative Example 1 after immersion for 15 days, and the inset is a schematic diagram of the coating equivalent circuit. It can be seen from the figure that the capacitance arc radius of the coating with 6% Cr3C2 particle content is the highest, followed by 7.5%, 4.5% and 3%, which is consistent with the results of the dynamic potential polarization test analysis in (1.2).

[0156] Continue to analyze the EIS experimental data in depth and fit the coating impedance spectrum, such as Fig.24As shown, in this simulation circuit, Table 4 is the fitting results of each component in the equivalent circuit of the coating impedance spectrum after immersion for 15 days. By observing Table 4, it can be found that the solution resistance R1 also fluctuates little during the experiment, and the coating with 6% Cr3C2 particle content shows the largest R2 value.

[0157] Table 4 Fitting results of components in the equivalent circuit of the coating impedance spectrum after immersion for 15 days

[0158]

[0159] A 15-day full immersion experiment was carried out in a simulated seawater environment. The coatings with different Cr3C2 particle contents were subjected to potentiodynamic polarization tests and electrochemical impedance spectroscopy tests at room temperature. The test results showed that after 15 days of full immersion, the coating with 6% Cr3C2 particle content still showed the best corrosion resistance. This phenomenon was also attributed to the low porosity of the coating, but the accumulation of corrosion products should also be considered. The pores are channels for simulated seawater to penetrate into the surface of the substrate, and the dense coating effectively blocks this penetration and inhibits the electrochemical corrosion reaction, thereby reducing the corrosion rate and the accumulation of corrosion products. Especially in the long-term corrosion process, the accumulation of corrosion products is more important, and these corrosion products usually accelerate the corrosion rate. It is hoped that this conclusion can provide some valuable help for the design and optimization of iron-based amorphous alloy coatings to cope with long-term corrosion in marine environments.

[0160] In summary, the corrosion resistance and corrosion process of amorphous composite coatings with different Cr3C2 particle contents in simulated seawater were studied by electrochemical corrosion. The following conclusions were drawn:

[0161] (1) By using simulated seawater as the electrolyte, the coatings with different Cr3C2 particle contents were subjected to open circuit potential test, potentiodynamic polarization test and electrochemical impedance spectroscopy test at room temperature. The three test results all showed that the coating with 6% Cr3C2 particle content exhibited the best corrosion resistance, which was attributed to the low porosity of the coating.

[0162] (2) After being fully immersed for 15 days, the coatings with different Cr3C2 particle contents were subjected to potentiodynamic polarization tests and electrochemical impedance spectroscopy tests. The coating with 6% Cr3C2 particle content still showed the best corrosion resistance.

[0163] (3) In the immersion experiment, scanning electron microscopy revealed that the surface remained flat on the first day. On the seventh day of immersion, pitting began to appear on the surface, but no corrosion products were found. After 15 days of immersion, corrosion products appeared on the surface. After removing these corrosion products, it was found that obvious pitting and cracks were formed on the surface. EDS analysis and XRD analysis confirmed that these corrosion products were mainly Fe2O3.

[0164] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An iron-based amorphous composite coating, characterized in that: The chemical composition includes FeCrMo amorphous coating and Cr3C2 particles dispersed in the FeCrMo amorphous coating; the mass content of Cr3C2 particles in the iron-based amorphous composite coating is 3-10%.

2. The iron-based amorphous composite coating according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the FeCrMo amorphous coating includes: Cr 25-27%, Mo 16-18%, C 2.0-2.5%, B 2.0-2.2%, and Fe 50.3-55%.

3. The iron-based amorphous composite coating according to claim 1 or 2, characterized in that: The thickness of the iron-based amorphous composite coating is 200-400 μm.

4. The method for preparing the iron-based amorphous composite coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: The mixed powder is used to perform supersonic flame spraying on the surface of a metal substrate to form an iron-based amorphous composite coating; the mixed powder includes FeCrMo amorphous powder and Cr3C2 particles, and the mass content of the Cr3C2 particles in the mixed powder is 3-10%.

5. The preparation method according to claim 4, characterized in that: The particle size of the FeCrMo amorphous powder is 15-53 μm.

6. The preparation method according to claim 4, characterized in that: The particle size of the Cr3C2 particles is 35-55 μm.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The supersonic flame spraying adopts high-speed air fuel technology, and the process conditions include: oxygen flow rate 1500-2200 SCFH, spraying distance 250-350 mm, fuel flow rate 5-8 GPH, powder feeding rate 30-40 g / min, and carrier gas flow rate 10-15 L / min.

8. The preparation method according to claim 7, characterized in that: The fuel for supersonic flame spraying includes one or more of kerosene, propylene, natural gas and liquefied petroleum gas.

9. The preparation method according to claim 4, characterized in that: The metal substrate is sandblasted and then preheated before use.

10. Use of the iron-based amorphous composite coating according to any one of claims 1 to 3 or the iron-based amorphous composite coating prepared by the preparation method according to any one of claims 4 to 9 as a protective layer.

Citation Information

Patent Citations

  • Ceramic-phase-containing iron-based amorphous nanocrystalline composite coating and preparation thereof

    CN101298654A

  • Corrosion-resistant iron-based amorphous alloy coating, preparation method and application thereof

    CN112899587A

  • Amorphous coating and preparation method thereof, pot and cooking equipment

    CN116411229A

  • Composite spray coating film, composite powder for spray coating, formation method for composite spray coating film, and composite powder spray coating film member

    JP2014173180A

  • Fe-BASED AMORPHOUS ALLOY HAVING HIGH CARBON CONTENTS

    KR1020140108383A